Shock Wave Therapy Associated with Eccentric Strengthening vs Isolated Eccentric Strengthening for Achilles Insertional Tendinopathy Treatment: A Double Blinded Randomized Clinical Trial. Issue 1 (January 2022) - Mansur, Nacime S.; Carrazzone, Oreste L.; Matsunaga, Fabio Teruo; Faloppa, Flávio; Sugawara Tamaoki, Marcel Jun
Category: Sports; Other Introduction/Purpose: Lack of consensus inhibits Achilles insertional tendinopathy (AIT) management. The condition is usually treated with eccentric exercises (EE), despite its absence of satisfactory and standing results. Shock wave therapy (SWT) was presented as an alternative, but it is still supported by a paucity of studies that shows moderate outcomes. The purpose of this study is to determine if the association of shock wave therapy (SWT) with the eccentric exercises (EE) protocol improve rates of pain and function in patients with AIT. Methods: This was a single-centre, double blind, placebo-controlled, in parallel groups, randomized clinical trial. 119 patients diagnosed with AIT, were evaluated, and enrolled in the study from February 2017 to February 2019. They were divided in two treatment groups, SWT associated to EE (SWT group) and EE associated to sham (CON group). Three sessions of radial shockwaves (or sham) separated by 2 weeks and eccentric training for three months were applied. The primary outcome was the Victorian Institute of Sport Assessment-Achilles questionnaire (VISA-A) at 24 weeks. Secondary outcomes included the Visual Analogue Scale (VAS), Algometry, the Foot and Ankle Outcome Score (FAOS) and the 12 Item Short Form Health Survey (SF-12). Results: Both groups showed significant improvement with the corresponding treatment in the study period. However, there were no between-group differences (all ps > 0.05) in any of the outcomes. At the 24th week evaluation, the SWT group exhibited a mean VISA-A of 63.2 (CI 8.0) and the CON group of 62.3 (CI 6.9), p=0.876. Failures were higher in the SWT (38.3% to 11.5%, p=0.002) and recurrences were superior in the CON side (34.6% to 17.0%, p=0.047). There were no complications. Conclusion: Extracorporeal shockwave therapy does not potentialize the effects of eccentric strengthening in the management of Achilles insertional tendinopathy.